Rehearsing the state : the political practices of the Tibetan government-in-exile - McConnell, Fiona (RGS-IBG book series., 2016)
Controversy has surrounded the legal, territorial, and political status of Tibet for decades. How does the Tibetan Government-in-Exile (TGiE)ù in spite of a complete lack of legal recognitionù continue to enact state-like functions from the hill town of Dharomsala, India? Rehearsing the State: The Political Practices of the Tibetan Government-in-Exile presents a comprehensive investigation of the institutions, performances, and actors through which the exiled Tibetan communityùthis active state-in-waiting ù is experimenting, modifying, and rehearsing state practices. Based on ethnographic research on the TGiE and in Tibetan communities based in India, chapters bring critical theories of the state into dialogue with geographies of temporality to develop the idea of rehearsal through the exploration of spaces, roles, scripts, and audiences in the performance of exile statecraft. A wide range of issues are explored, including how state-like functions are enacted without legal jurisdiction over territory, ways in which futures are made present alongside prolonged waiting, and what happens to these anticipatory logics when the time frame is extended indefinitely. Illuminating and thought-provoking, Rehearsing the State offers timely insights into exile Tibetan politics while making a significant contribution to wider issues of critical state theory and the politics of displacement. --Book Jacket.